Road Infrastructure Inequality and Dropout Rates in Isolated Areas: Tracking the Indonesian Literature - I Made Suraharta (AL-ISHLAH: Jurnal Pendidikan, 2021)
Limited access to land transportation due to the lack of adequate road infrastructure in isolated and remote areas contributes to the high dropout rates of students in such areas. Therefore, the government always promotes road infrastructure development in these isolated areas, increases economic growth, and provides development access in other sectors, including the education sector. Education is not just an obligation as the discourse echoed by the government, but it should be a right given by the state to its people. Therefore, this study aims to analyze the impact of infrastructure development inequality in isolated areas and the education sector, especially in increasing the dropout rates. This study uses a systematic literature review to investigate five writings. The data was driven using the assistance of  Ferreira Gignoux’s (2011) theory of inequality of opportunity. The findings show that the construction of road infrastructure in remote and isolated areas dramatically affects the distribution of education, including efforts to reduce the dropout rate of children. The forms of benefits obtained by building road infrastructure are easy to access for students to places of learning, easy access for teachers and educators to reach isolated areas, ease of procurement of school facilities and infrastructure, which has an impact on increasing the quality of education and finally can help the community's economy so that children can be financed so as not to drop out of school.